Penerapan Data Mining Dalam Menentukan Penerima Beasiswa UPZ (Unit Pengumpulan Zakat) Menggunakan Algoritma K-Means - Sri Astuti; Samsudin samsudin; Triase triase (Universitas Sriwijaya, 2021)
Data Mining is a technology used in data processing. This data mining technique is able to dig up information from old data or piles of data into useful information such as student data at a university. Student Data in Higher Education has a student data mine which, if processed using data mining techniques, will produce new and useful information such as information on the eligibility of a student in getting a scholarship. One of them is the zakat collection unit scholarship at universities in North Sumatra. The difficulty faced by the zakat collection unit scholarship selection committee is determining the eligibility for the zakat collection unit scholarship recipients because the selection process is still manual, so the selection process takes a long time. Based on the existing problems, a data mining system was made using the k-means algorithm that was able to classify students who deserved a web-based zakat collection unit scholarship using the PHP programming language. The purpose of this system is to make it easier and faster for the UPZ selection committee to determine the eligibility of zakat collection unit scholarship recipients